Development of moringa oleifera stem fiber fabric blended with polyester and cotton for bags - Bailon, Carina Ysabel R.; Caragay, Kristyn T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
The textile industry is currently looking for sustainable ways to produce apparel and accessories as a result of the growing market for sustainable products (SolarCity, n.d). One way to address this is by developing natural raw materials. The moringa oleifera (MO) is a tropical plant that is abundant in the Philippines. This can be grown sustainably without the use of harmful chemicals and too many resources. Hence, the plant can be a source of an ecofriendly textile. This experimental research aimed to characterize MO fibers and to develop a fabric suitable for bags. The MO fibers that were extracted from the stem were white and their length depended on the length of the stem but averages 5 centimeters. The fibers produced had low tensile strength which affected converting these fibers to yarn. They were blended with polyester and cotton because they crack or break easily when dried. The fabric was woven with 20% MO, 20% cotton and 60% polyester. The fabric was seen to be best converted into a clutch bag because of its characteristics. The bag production was feasible but encountered problems in applying adhesives because of its roughness. The functional and aesthetic properties of the bag were evaluated by three bag designers. They all agreed that the material was feasible for bag design but the roughness needs to be addressed. They also suggested exploring decorative finishes and dyeing. It was also found that the production of the fabric was sustainable as the resources used were minimal, while the wastes produced are not harmful to the environment. The cost is minimal, although the extraction of the fiber is labor intensive. The researcher recommends to improve the tensile strength, address the roughness and experiment on decorative finishes on the MO fabric blend.
Submitted June 2016.
Thesis (BS Clothing Technology) -- University of the Philippines Diliman.
Keywords: Plant fibers -- Philippines; Moringa Oleifera